MITOP: database for mitochondria-related proteins, genes and diseases. - Scharfe, C (1999)
The MITOP database http://websvr.mips.biochem.mpg. de/proj/medgen/mitop/ consolidates information on both nuclear- and mitochondrial-encoded genes and their proteins. The five species files- Saccharomyces cerevisiae, Mus musculus, Caenorhabditis elegans, Neurospora crassa and Homo sapiens -include annotated data derived from a variety of online resources and the literature. A wide spectrum of search facilities is given in the interelated sections 'Gene catalogues', 'Protein catalogues', 'Homologies', 'Pathways and metabolism', and 'Human disease catalogue' including extensive references and hyperlinks for each entry. Precomputed FASTA searches using all the MITOP yeast protein entries and a list of the best EST hits with graphical cluster alignments related to the yeast reference sequence are presented. The MITOP orthologue tables with cross-listing to all the protein entries for each species in the database facilitate investigations into interspecies homology. A program (MITOPROT) is available to identify mitochondrial targeting sequences and graphical depictions of several important mitochondrial processes are included. The 'Human disease catalogue' lists a total of 101 disorders related to mitochondrial protein abnormalities, sorted by clinical criteria and age of onset.